ASSESSMENT OF BIODIVERSITY AND ECOSYSTEM SERVICES UTILIZED LIFE-CYCLE ASSESSMENT AND ENVIRONMENTAL ECONOMIC VALUATION: CASE STUDY OF WOODEN AND STEEL FRAMED HOUSE - ITO, Hideyuki; HAYASHI, Kiichiro (SOCIOTECHNICA, 2015)
Existing Life-Cycle Impact Assessment (LCIA) approach has looked around only the impact on land area by acquiring feedstock and occupation of factories without sufficiently addressing the importance of assessing ecosystem services. Therefore, the purpose of this study is to propose an assessment method for ecosystem services using assessment results of existing studies through a case study of wooden and steel framed house used domestic lumber. Thus, firstly we estimated the total impacted land area by each land use type throughout the lifecycle of both a wooden and a steel-framed house. We then made an inventory to quantify the economic value of ecosystem services by each impacted ecosystem type. As a result, we could indicate the basic outline of a future direction for evaluating ecosystem services comprehensively.